CO2 Laser‐Induced Graphene with an Appropriate Oxygen Species as an Efficient Electrocatalyst for Hydrogen Peroxide Synthesis. Issue 60 (25th August 2022) - Fan, Mengmeng; Xu, Jing; Wang, Yan; Yuan, Qixin; Zhao, Yuying; Wang, Zeming; Jiang, Jianchun
Abstract: Oxygen species functionalized graphene (O−G) is an effective electrocatalyst for electrochemically synthesizing hydrogen peroxide (H2 O2 ) by a 2 e − oxygen reduction reaction (ORR). The type of oxygen species and degree of carbon crystallinity in O−G are two key factors for the high catalytic performance of the 2 e − ORR. However, the general preparing method of O−G by the precursor of graphite has the disadvantages of consuming massive strong oxidant and washing water. Herein, the biomass‐based graphene with tunable oxygen species is rapidly fabricated by a CO2 laser. In a flow cell setup, the laser‐induced graphene (LIG) with abundant active oxygen species and graphene structure shows high catalytic performance including high Faraday efficiency (over 78 %) and high mass activity (814 mmolgcatalyst −1 h −1 ), superior to most of the reported carbon‐based electrocatalysts. Density function theory demonstrates the meta‐C atoms at nearby C−O, O−C=O species are the key catalytic sites. Therefore, we develop one facile method to rapidly convert biomass to graphene electrocatalyst used for H2 O2 synthesis. Abstract : Biomass‐based graphene with active oxygen species is rapidly fabricated by a CO2 laser method. The laser‐induced graphene shows a high catalytic performance in 2 e − oxygen reduction reactions to synthesize H2 O2 including high Faraday efficiency (over 78 %) and mass activity (814 mmolgcatalyst −1 h −1 ) in alkaline solution, superior to most of the reported carbon‐based electrocatalysts. As demonstrated by density function theory simulations, the high catalytic sites are attributed to the meta‐C atoms with charge accumulation at nearby C−O and O−C=O species.